Dissemination and Assistance of E-Marketing and Making Smart MSME Cards in Probolinggo City - Tumini Tumini; Seger Prihantono; Khusnik Hudzafidah; Dela Ayu Octaryanti (TGO Journal of Community Development, 2023)
The purpose of this community service activity is to provide an understanding of the importance of e-marketing for business actors so that the businesses they establish develop more by expanding the existing market share. On the other hand, the government also supports existing MSMEs by issuing Smart MSMEs Cards that reach MSME owners. So these two things are a strong reason for us to hold an e-Marketing Socialization and Smart MSME Card Making by inviting several MSME owners in the Jrebeng Kidul Village, Wonoasih District, Probolinggo City. The method used in the form of initial observation and data collection. Then socialization and mentoring activities for MSMEs. The results of the activity show that there is an increase in the ability of MSME actors in online marketing (e-marketing). In addition, the formation of a smart MSME card that can reach between MSME communities in the city of Probolinggo.